2018
DOI: 10.17130/ijmeb.2018137584
|View full text |Cite
|
Sign up to set email alerts
|

Kültür Boyutlari İle Online Alişveri̇ş Davranişi İli̇şki̇si̇: Bi̇reysel Yeni̇li̇kçi̇li̇k Ve Güveni̇n Aracilik Etki̇si̇

Abstract: Elektronik platformlara olan güvenin artmasının ve yenilikçi uygulamaların tüketicileri cezbetmesinin yanında, kişilerin benimsedikleri kültürün de online alışverişte etkili olduğu varsayılmaktadır. Çünkü toplumun sahip olduğu kültürel özellikler, bireye yansımaktadır. Farklı kültürel özellikler sonucu, bireylerin satın alma davranışları da farklılaşmaktadır. Çalışmada, Hofstede'in kültür boyutlarının online alışverişe etkisi, Yapısal Eşitlik Modellemesi ile araştırılmıştır. 316 kişiden anketle veri toplanmış,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There are studies on the dimensions of culture. Esen et al [17] found that uncertainty avoidance has a direct effect on purchasing behavior, while collectivism has an indirect effect. Danish et al [18] concluded that knowledge management practices have a positive effect on organizational effectiveness and that this effect is moderated by organizational culture.…”
Section: Literature Review 21 Organizational Culturementioning
confidence: 99%
“…There are studies on the dimensions of culture. Esen et al [17] found that uncertainty avoidance has a direct effect on purchasing behavior, while collectivism has an indirect effect. Danish et al [18] concluded that knowledge management practices have a positive effect on organizational effectiveness and that this effect is moderated by organizational culture.…”
Section: Literature Review 21 Organizational Culturementioning
confidence: 99%